2018
DOI: 10.3233/prm-180555
|View full text |Cite
|
Sign up to set email alerts
|

Update on bone fragility in spina bifida

Abstract: BACKGROUND CONTEXT: Patients with spina bifida (SB) are at risk for pathological fractures and low bone mineral density (BMD). PURPOSE AND METHODS: This article reviews the literature and provides a comprehensive overview of how the characteristics of SB and its associated comorbidities intersect with bone fragility to identify possible pathophysiological mechanisms of fractures and low BMD. RESULTS: Bone fragility occurs early in the life of patients with SB as a result of a disturbance that determines change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 120 publications
(385 reference statements)
0
7
0
Order By: Relevance
“…Multiple studies using DXA have reported lower BMD in patients with higher lesion levels and lower ambulatory ability. (14)(15)(16)(17)19,21,22) The most striking difference between neurosegmental subgroups observed in our study was lower cancellous density in the metaphyses in the lumbar groups compared with the sacral group. Despite this lower cancellous density, weighted area, a surrogate for total bone mass, was similar among the neurosegmental groups.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Multiple studies using DXA have reported lower BMD in patients with higher lesion levels and lower ambulatory ability. (14)(15)(16)(17)19,21,22) The most striking difference between neurosegmental subgroups observed in our study was lower cancellous density in the metaphyses in the lumbar groups compared with the sacral group. Despite this lower cancellous density, weighted area, a surrogate for total bone mass, was similar among the neurosegmental groups.…”
Section: Discussionmentioning
confidence: 55%
“…(14)(15)(16)(17)(18)(19)(20)(21) These studies have generally found reduced BMD in persons with SB, particularly in the lower extremities. (22) BMD decreases with higher levels of neurologic involvement and lower ambulatory ability. (14)(15)(16)(17)19,21) Prior fracture and periods of immobilization also reduce BMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis is frequently seen below the level of the lesion and fractures are commonly seen due to smaller bones, lower bone mass, and mineralization deficits associated with endocrinologic and metabolic abnormalities, particularly during critical periods of bone deposition [ 51 , 52 ]. Those with higher SB lesions who are non-ambulatory tend to have decreased activity levels, higher body fat levels, and more contractures, all lending to an increased fracture risk [ 52 ].…”
Section: Spina Bifidamentioning
confidence: 99%
“…Lennox-Gestaut syndromeSevere childhood seizure syndrome with multiple causes, including genetic mutations, perinatal injuries, cortical malformations, infections, and tumors Unclear whether OP results from the underlying disease, external factors (antiepileptics, immobility, malnutrition), or both14 Spina bifida Congenital disorder caused by incomplete closure of the vertebral column ± meninges during embryogenesis Decreased bone strength resulting from smaller bones, mineralization defects, and lower bone mass15 OP, osteoporosis.Review ArticleSouthern Medical Journal • Volume 114, Number 4, April 2021…”
mentioning
confidence: 99%